Citizen Characteristics and Their Participation in Food Safety Social Co-governance: Public Health Implications - Chen, Xiujuan; Qin, Ke; Wu, Linhai (Frontiers in Public Health, 2021)
Objective: Given that positive psychological capital motivates citizens to actively participate in social affairs, this study aims to provide insight into food safety governance in China by empirically determining which individual characteristics are associated with positive psychological capital for actively participating in social co-governance. Methods: A questionnaire-based survey was undertaken between Dec 5 and Dec 10, 2020. The study participants were residents of Wuxi in China over the age of 18 years. A validated and pretested questionnaires elicited responses with the participants. Student’s t-test and one-way analysis of variance were performed to determine which individual characteristics are significantly correlated with the psychological capital of citizens who participate in co-governance. Post-hoc multiple comparisons were performed for each individual characteristic with a significant correlation to determine which categories of these characteristics yield the significant differences. The data of the study were analyzed with IBM SPSS Statistics 24.0. Results: A total of 752 completed responses were received. Most respondents were females (52.39%), aged 26 to 45 (66.09%), married (70.48%), company employees (44.28%), and in good health (89.76%). Most had a household size of 3 (55.98%), a bachelor’s degree (40.96%), a personal annual income of more than 100,000 yuan (26.46%), no children aged under 18 (50.27%) or pregnant woman (93.22%) in their households. Data analysis indicated that education, income, and health status significantly influence the psychological capital of citizens to participate in co-governance. Citizens with high education, high income, and good health status have higher psychological capital to participate in co-governance. Conclusion: The present study suggested citizens are likely to actively participate in food safety social co-governance only when they have at least one of three characteristics: (a) higher than average income in their city of residence; (b) a bachelor’s degree or higher education; or (c) good health. Therefore, motivating citizens to participate in co-governance is a long-term process in China. The fundamental strategy is to increase the income of citizens, especially low-income groups, promote education to improve food safety literacy of the public, and improve sanitation and public health.